2016
DOI: 10.3389/fnbeh.2016.00150
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Theta Burst Over M1 May Increase Peak Power of a Wingate Anaerobic Test and Prevent the Reduction of Voluntary Activation Measured with Transcranial Magnetic Stimulation

Abstract: Despite the potential of repetitive transcranial magnetic stimulation (rTMS) to improve performances in patients suffering from motor neuronal afflictions, its effect on motor performance enhancement in healthy subjects during a specific sport task is still unknown. We hypothesized that after an intermittent theta burst (iTBS) treatment, performance during the Wingate Anaerobic Test (WAnT) will increase and supraspinal fatigue following the exercise will be lower in comparison to a control treatment. Ten subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…In a previous study, after a fatiguing task, we also observed an attenuated reduction in VA TMS , probably induced by brain stimulation, but not an attenuated reduction in Ptw. Similarly to the present study, the attenuation in VA TMS reduction was not accompanied by an immediate effect on MVC [ 28 ]. Thus, in the present experimental context, the main limiting factors of performance following the time-trial seem to have more peripheral than central origin.…”
Section: Discussionsupporting
confidence: 85%
“…In a previous study, after a fatiguing task, we also observed an attenuated reduction in VA TMS , probably induced by brain stimulation, but not an attenuated reduction in Ptw. Similarly to the present study, the attenuation in VA TMS reduction was not accompanied by an immediate effect on MVC [ 28 ]. Thus, in the present experimental context, the main limiting factors of performance following the time-trial seem to have more peripheral than central origin.…”
Section: Discussionsupporting
confidence: 85%
“…Since MEP amplitudes were not normally distributed, non-parametric tests were used to compare them. We used Mann–Whitney U -tests with Bonferroni correction to directly compare MEP amplitudes at each time point among protocols, based on the assumption that iTBS increases these amplitudes ( Chung et al, 2016 ; Giboin et al, 2016 ). In addition, the Spearman rank correlation coefficient was used to analyze the relationship between RI at Post0 and the pre-PES of the MEP amplitude.…”
Section: Resultsmentioning
confidence: 99%
“…Intermittent theta burst stimulation (iTBS) is a repetitive transcranial magnetic stimulation (rTMS) protocol that uses a short stimulation period (190 s). iTBS alters motor cortex excitability comparably to other rTMS and tDCS protocols that involve longer stimulation (10 or 20 min) ( Huang et al, 2005 ; Jeffery et al, 2007 ; McAllister et al, 2009 ; Goldsworthy et al, 2012 ; Tatemoto et al, 2013 ), and is also capable of enhancing motor cortical excitability evoked by stimulation of the cortical lower limb area ( Jeffery et al, 2007 ; Tatemoto et al, 2013 ; Giboin et al, 2016 ). These observations suggest that iTBS might be usable to modify PES-induced plasticity, and furthermore the brief stimulation used in this protocol makes it more suitable than other protocols for examining the influences of the timing and magnitude of motor cortical excitability changes on the spinal plasticity induced by PES.…”
Section: Introductionmentioning
confidence: 97%
“…Since the movement was not resisted and the mass of the index finger is small (the goniometer is also very light), we have discussed our results as stemming from an unresisted movement, but it is true that the resistance for the extensors and the flexors in our task is not exactly the same. This is important since repetitive movements against higher levels of resistance might present different evolution of muscle excitability and processes related to muscle force production 34 .…”
Section: Discussionmentioning
confidence: 99%